Strategi Promosi Madrasah melalui Pemanfaatan Media Online citrasumsel.com - Novriansyah, M. Anasrul Dwi; Annur, Saipul; Afriantoni, Afriantoni (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Promotion is an essential instrument for improving a school's image and competitiveness. Online media has become a mass communication tool capable of expanding information reach and accelerating the delivery of messages to the public. This study aims to analyze the strategy for developing madrasa promotion through the online media citrasumsel.com in the education column. This study used a qualitative approach. Data were obtained through interviews and observations at the Private Madrasah Aliyah Yayasan Perguruan Islam Ihsaniyah (MAS YPII). The results showed that the promotional strategy showed significant progress. Its significance was seen in the increased number of applicants and the positive public perception of the madrasa's credibility and character. In addition, the promotional strategy was carried out by training students to write, establishing formal partnerships, and improving the madrasa's image through citrasumsel.com, utilizing the madrasa's website and social media, visits to junior high schools/Islamic junior high schools, and installing banners.